A inibição central do TNF-α reduz a pressão arterial via inibição do tônus simpático em ratos com hipertensão renovascular - Galvão, Alynne Carvalho (2016)
Over the years, evidence suggests a relationship between angiotensin II and proinflammatory cytokines, such as TNF-α, in the pathogenesis of cardiovascular diseases, including hypertension. Recently, the focus of new studies has been to understand the central mechanisms involved in the maintenance of events that trigger the increase in sympathetic activity in hypertension. The aim of this study was to evaluate the effects of central inhibition of TNF-α on blood pressure, sympathetic tone, baroreflex sensitivity and oxidative stress in RVLM of rats with renovascular hypertension (2K1C). A silver clip (internal diameter = 0.2 mm) was implanted in the right renal artery for hypertension induction (for six weeks). The animals were divided in three groups, Sham, 2K1C and 2K1C + PTX. This last group received central infusion (in the lateral ventricle) of pentoxifylline (30 nmol/uL/h), a TNF-α inhibitor, by osmotic minipumps for 14 days, four weeks after the silver clip implant. The catheters were implanted in the abdominal aorta and caudal venus cava to register the cardiovascular parameters and drug administration, respectively. Phenylephrine (8 μg / kg, i.v.) and sodium nitroprusside (25 μg / kg, i.v.) were administered to evaluate the baroreflex sensitivity, which was also evaluated by the sequence method for spontaneous baroreflex (Cardioseries v.2.4.). An indirect evaluation of autonomic modulation of vascular resistance was performed by spectral analysis of the low-frequency component (LF) of systolic blood pressure (SBP) (Cardioseries v.2.4.), while the vascular sympathetic tone was evaluated by ganglionic blockade with hexamethonium (30 mg/kg, i.v.). For superoxide accumulation measurements in the RVLM, was used the dihydroethidium technique (DHE), expressed by relative fluorescence (arbitrary units). The 2K1C group showed an increase in mean arterial pressure (MAP) compared to the Sham group (171 ± 11 vs. 113 ± 5 mm Hg; n = 8, p <0.05). Hypertensive animals showed a decrease in baroreflex sensitivity in relation to normotensive animals in the analysis by Oxford method (-1.30 ± 0.10 vs. -2.59 ± 0.17 bpm.mmHg−1; n = 8; p < 0.05) and by sequence method (0.58 ± 0.08 vs. 1.48 ± 0.04 ms/mmHg; n = 8; p<0.05). The evaluation of sympathetic vasomotor activity by spectral analysis showed an increase of LF component in 2K1C animals when compared to Sham group (9.16 ± 0.52 vs. .,32 ± 0.38 mmHg2; n = 8; p<0.05). The increase was also observed in animals 2K1C when compared to normotensive in relation to the variation in MAP after blockade with hexamethonium (-60 ± 5 vs. -33 ± 2 ΔmmHg; n = 8; p < 0.05) and superoxide accumulation in RVLM (18 ± 2 vs. 4 ± 1; n = 8; p < 0.05). When compared to 2K1C group that not received infusion of pentoxifylline (n=8), central inhibition of TNF-α for 14 days in animals with renovascular hypertension (n=6) reduces the mean arterial pressure (171 ± 11 vs. 131 ± 2 mmHg; p <0.05) and the superoxide accumulation in RVLM (18 ± 2 vs. 8 ± 1; p < 0.05). Furthermore,animals of 2K1C+PTX group had an improve in baroreflex sensitivity and reduced sympathetic tone when compared to 2K1C group (-34 ± 3 vs. -60 ± 5 ΔmmHg, n=8; p< 0.05). Additionally, spectral analysis of LF (PAS) showed that the central inhibition of TNF-α decreased this component in 2K1C+PTX group when compared to 2K1C (4.90 ± 0.66 vs. 9.16 ± 0.52 mmHg2; p < 0.05). Based on our results, we suggest the involvement of TNF-α in the maintenance of sympathetic vasomotor activity and oxidative stress in RVLM in renovascular hypertension model (2K1C).